Muscle Synergies in Response to Biofeedback-Driven Gait Adaptations in Children With Cerebral Palsy - Booth, Adam T. C.; van der Krogt, Marjolein M.; Harlaar, Jaap; Dominici, Nadia; Buizer, Annemieke I. (Frontiers in Physiology, 2019)
Background: Children with cerebral palsy (CP) often show impaired selective motor control (SMC) that induces limitations in motor function. Children with CP can improve aspects of pathological gait in an immediate response to visual biofeedback. It is not known, however, how these gait adaptions are achieved at the neural level, nor do we know the extent of SMC plasticity in CP. Aim: Investigate the underlying SMC and changes that may occur, when gait is adapted with biofeedback. Method: Twenty-three ambulatory children with CP and related (hereditary) forms of spastic paresis (Aged:10.4 ± 3.1, 6-16 years, M:16/F:9) were challenged with real-time biofeedback to improve step length, knee extension and ankle power while walking on an instrumented treadmill in a virtual reality environment. The electromyograms of eight superficial muscles of the leg were analysed and synergies were further decomposed using nonnegative matrix factorization using 1 to 5 synergies, to quantify SMC. Total variance accounted for (tVAF) was used as a measure of synergy complexity. An imposed four synergy solution was investigated further to compare similarity in weightings and timing patterns of matched paired synergies between baseline and biofeedback trials. Results: Despite changes in walking pattern, changes in synergies were limited. The number of synergies required to explain at least 90% of muscle activation increased significantly, however, the change in measures of tVAF1 from baseline (0.75 ± 0.08), were less than ± 2% between trials. In addition, within-subject similarity of synergies to baseline walking was high (> 0.8) across all biofeedback trials. Conclusions: These results suggest that while gait may be adapted in an immediate response, SMC as quantified by synergy analysis is perhaps more rigidly impaired in CP. Subtle changes in synergies were identified, however, it is questionable if these are clinically meaningful at the level of an individual. Adaptations may be limited in the short term and further investigation is essential to establish if long term training using biofeedback leads to adapted SMC.